FRI0442 APPROPRIATE USE OF SEROLOGY TESTS FOR THE DIAGNOSIS OF LYME DISEASE. EXPERIENCE IN AN URBAN AREA. (2nd June 2020) - Lobo Prat, D.; Sainz Comas, L.; Pomar, V.; Millán Arciniegas, A. M.; Park, H.; García-Guillén, A.; Jeria, S.; Laiz, A.; Magallares, B.; Castellví, I.; Moya, P.; Díaz-Torné, C.; et al.
Abstract : Background: Lyme disease (LD) is a multisystemic animal-borne disease caused by spirochetes of the Borrelia burgdorferi s.l complex and transmitted by ticks of the species Ixodes ricinus . In Spain, most cases occur in rural areas of the north-east region with a peak of maximum incidence between spring and early autumn. The diagnosis is based on a history of potential exposure to ticks, the recognition of characteristic clinical manifestations and serological testing. Objectives: To assess the suitability of serological study for the diagnosis of LD in an urban area. Methods: Retrospective observational study that included all LD serology tests made between April 2017 and September 2019 at a tertiary hospital in Barcelona covering a population of 450, 000 people. Demographic data and the medical department that requested the serology test were collected along with serology test results. The medical records of patients with positive serology were consulted to identify which patients were finally diagnosed with LD along with their clinical manifestations, treatment and outcome. Results: A total of 574 serological tests were included and 78 (13.59%) of them were positive. Only 1.04% (6) of all serological tests belonged to patients finally diagnosed with LD. The department that made most requests was Neurology (37.3%) followed by Infectious Diseases (21%), Internal Medicine (14.5%), Emergency Medicine (4.7%), Dermatology (4.5%), Critical Care Medicine (2.3%) and Rheumatology (2.1%). 50% of the diagnosed patients were women with a mean age of 57.7±7.7DE years. In 50% of diagnosed cases, patients remembered a tick bite during activities in the mountain or rural areas. The most common clinical manifestations were erythema migrans (67%), non-inflammatory arthralgias (50%), fatigue and malaise (67%), together with one case of meningoencephalitis and one of knee monoarthritis. All diagnosed patients received antibiotic treatment with ceftriaxone (33%) or doxycycline (66%). Only one patient presented post-Lyme syndrome. The serological test for LD in our center had a total individual cost of 15.75 eur, so the cost of the 574 requests was 9, 040.5 eur. 7, 812 eur corresponded to negative results and 1, 134 eur to false positive results. Conclusion: Our study indicates the overuse of diagnostic testing for LD with implications for patient care and cost-effective health management. In the absence of a history of potential exposure to infected vector ticks or characteristic clinical manifestations, unnecessary microbiological tests should not be performed. Disclosure of Interests: David Lobo Prat: None declared, Luís Sainz Comas: None declared, Virginia Pomar: None declared, Ana Milena Millán Arciniegas: None declared, HyeSang Park: None declared, Andrea García-Guillén: None declared, Sicylle Jeria: None declared, Ana Laiz: None declared, Berta Magallares: None declared, Ivan Castellví Consultant of: Boehringer Ingelheim, Actelion, Kern Pharma, Speakers bureau: Boehringer Ingelheim, Actelion, Bristol-Myers Squibb, Roche, Patricia Moya: None declared, Cesar Díaz-Torné: None declared, Susana P. Fernandez-Sanchez: None declared, Hector Corominas: None declared